2021
DOI: 10.25165/j.ijabe.20211402.5261
|View full text |Cite
|
Sign up to set email alerts
|

Wind pressure acting on greenhouses: A review

Abstract: Greenhouses are widely used in agricultural and horticultural production. With the characteristics of lightweight, small stiffness and high flexibility, greenhouses are sensitive to wind loads. In the calculation of wind loads, the wind pressure coefficient (Cp) is essential. The rationality of the value directly affects the safety and economy of greenhouses. Therefore, the Cp values estimation is one of the most important issues in the design of greenhouses. In order to make full use of the existing research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Sakiyama et al [13] provided an overview of natural ventilation investigations with respect to thermal comfort, the efficiency of energy usage, and indoor air quality. Wang et al [14] summarized the wind pressure coefficients on the surface of different greenhouse types. Zhong et al [15] discussed papers relevant to single-sided natural ventilation.…”
Section: (G1))mentioning
confidence: 99%
See 1 more Smart Citation
“…Sakiyama et al [13] provided an overview of natural ventilation investigations with respect to thermal comfort, the efficiency of energy usage, and indoor air quality. Wang et al [14] summarized the wind pressure coefficients on the surface of different greenhouse types. Zhong et al [15] discussed papers relevant to single-sided natural ventilation.…”
Section: (G1))mentioning
confidence: 99%
“…Typical Chinese solar greenhouses (CSG) have horizontal roof openings. However, the measured wind pressure coefficients of CSG were only used to evaluate the wind load of the greenhouses [14] and to deduce the critical wind speed for wind disasters in various areas of the facility [62][63][64]. The wind pressure coefficient of CSG is often calculated using a scale model with the vents completely closed in the wind tunnel.…”
Section: Displacement Ventilationmentioning
confidence: 99%
“…At present, the main greenhouse design method is the quasi-static design method, which uses the equivalent static wind load and snow load. Many studies have used this method to simulate and evaluate the wind and snow resistance performance of different types of greenhouses and found that this method has high accuracy in low-rise buildings and simple greenhouse structures [5] .…”
Section: Introductionmentioning
confidence: 99%
“…There are currently three main methods to determine wind pressure coefficients, i.e., field experiment, wind tunnel test, and computational fluid dynamics (CFD). These methods were compared and presented, and the effects of greenhouse type, greenhouse roof angle and roof spacing were discussed respectively to determine the wind pressure on low-rise buildings or greenhouses in [11][12][13][14]. In these documents, Agronomy 2023, 13, 553 2 of 19 only Wang et al [14] mentioned the impact of topographic factors such as mountain terrain on greenhouse partial pressure, but they still did not give a specific research plan.…”
Section: Introductionmentioning
confidence: 99%